Analyze Maternal Mortality Factors Causes in Indramayu Regency West Java - Linda Yusanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Maternal mortality in Indramayu Regency is still high. There is an increase of maternal mortality with the mean 52,5 cases. Recording and reporting of maternal mortality conducted through the Audit of maternal prenatal. Recording and reporting an activity of maternal mortality has developed several instruments, one of them is Maternal Verbal Autopsy. Causative factors of maternal mortality that can be prevented divided into four categories; Factors associated with health workers, the patient's factor, administration/ availability of infrastructures factors and transportation/ reference factors. The aim of research was to analyze the characteristics of patients, birth attendant factors and referral factors that contribution in the maternal mortality direct causes. The research used descriptive analytical method which is conducted in Indramayu Regency. The sample used as many as 57 cases were taken by total sampling and selected as a research subject as much as 56 cases. Analysis of the results was done by using univariate, bivariate analysis Chi-Square test. The result with Univariate obtained cases of hypertension in pregnancy is the cause that is 47,36%. Bivariate analysis obtained that there is a significant association of parity factors to direct causes of maternal mortality especially hypertension in pregnancy with a value (ρ 0.05). The conclusion of the research, there is a meaningful relationship between parity factors and maternal mortality direct causes especially hypertension in pregnancy; meanwhile there is no relationship on the factors of patient characteristics, and birth attendant, administration/ infrastructure and referral to maternal mortality direct